The Role of the Village Fund Program in Alleviating Poverty in Rural Areas - Sari, Jayanti Armida; Sunarya, Amud; Darmanto (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to explore the role of the Village Fund Policy in alleviating poverty in Nagari Lingkuang Aua, Pasaman Barat Regency since poverty in Indonesia represents an urgent issue, particularly in rural areas that tend to exhibit higher poverty rates compared to urban regions. One of the government's policies for poverty eradication is the Village Fund Program. Methods: The study used the qualitative analytical approach to analyze how the Village Fund Program impacts poverty eradication in Nagari Lingkuang Aua. A case study approach was adopted, focusing on the Village Fund Policy. Primary data were compiled through semi-structured and unstructured interviews using purposive sampling techniques. In contrast, this study used existing literature to obtain secondary data from various sources. Results: The study results showed that the Village Fund Program played a significant role in reducing poverty levels in Nagari Lingkuang Aua. However, the effects tend to be short-termed, primarily focusing on fulfilling basic needs for families or individuals, such as food, education, or critical healthcare services. Conclusions: The study highlights the Village Fund Program's impact on reducing poverty in Nagari Lingkuang Aua, but it mainly offers short-term solutions. Sustainable poverty alleviation requires addressing poverty root causes through community-centered initiatives. Emphasizing community participation is indispensable, along with continual evaluation and adjusting fund allocation to align with developmental priorities for rural communities' growth and resilience.